Effect of a Shared Decision-Making-Based Exercise Management Program on Blood Glucose Control in Patients with Gestational Diabetes Mellitus - Liu B; Jia G; Cai F (Journal of Multidisciplinary Healthcare, 2025)
Bei Liu, Ge Jia, Fengcheng Cai Childbirth Center, Hangzhou Women’s Hospital, Hangzhou, 310008, People’s Republic of ChinaCorrespondence: Fengcheng Cai, Email ifb948@126.comObjective: To analyze the application of a shared decision-making (SDM)-based exercise management program in patients with gestational diabetes mellitus (GDM) and its impact on blood glucose control.Methods: A retrospective analysis was conducted on the clinical data of 88 GDM patients who delivered at the Hangzhou Women’s Hospitalbetween December 2022 and April 2024. Patients were divided into the control group (n=44, receiving conventional exercise management program) and the observation group (n=44, receiving SDM-based exercise management program). Compliance with medical advice, quality of life (DSQL), self-management ability (SDSCA), blood glucose indicators (FBG, 2 h PG, and HbAlc), adverse self-management behaviors, and maternal and neonatal pregnancy outcomes were compared between the two groups.Results: The observation group had higher rates of standardized medication use, scientific diet, regular blood glucose monitoring, adherence to exercise, and regular sleep patterns compared to the control group (P< 0.05). After intervention, the DSQL scores in both groups decreased, while the SDSCA scores increased, with the observation group showing a greater change (P< 0.05). The FBG, 2 h PG, and HbAlc levels were all lower after intervention in both groups, with the observation group showing a greater change (P< 0.05). The observation group had lower rates of poor blood glucose control, excessive weight gain during pregnancy, and unsatisfactory post-delivery oral glucose tolerance test (OGTT) compared to the control group (P< 0.05). The total incidence of adverse maternal pregnancy outcomes and neonatal adverse pregnancy outcomes was also lower in the observation group compared to the control group (P< 0.05).Conclusion: Compared to conventional exercise management programs, the SDM-based individualized exercise management program can further improve GDM patients’ compliance with medical advice, enhance self-management abilities and quality of life, regulate blood glucose control, and improve maternal and neonatal pregnancy outcomes.Keywords: shared decision-making, individualized exercise management plan, GDM, self-management ability, impact